Análisis prospectivo de los bioinsumos agrícolas en Colombia: una consulta a expertos - Avellaneda, Laura; Zambrano, Gregorio; Corina-Zambrano, Diana; Rebeca-Bonilla, Ruth (Revista Colombiana de Biotecnología, 2015)
Productivity and sustainability of agriculture in Colombia can be influenced positively through the use of biodiversity for the production of bioinoculants. They were analyzed in the medium and long term, the future scenarios generated by the regulations involved in the technological advancement of bio-products through the application of a Delphi survey, with the participation of 23 experts in bio-products, taking into account the three dimensions sustainable development. Based on this study, it was found that 65% of the experts believe that the impact of innovation and technological development of the use of bio- products in agricultural production, has a high economic impact with a significant level of agreement (≥0.05). Additionally, 65% selected as the best scenario, in which conditions that promote greater development, access and application of bio-products, so that the rate of adoption of technology is increased by the producers to make. In conclusion, beyond the level of technological development is necessary to revise the legislative process for the marketing of bio-products, it was clear that the future success of the industry in the production of biological products depend on the management of innovative enterprises, efficient marketing thereof, education and transfer to producers and the progress of the investigation.

La productividad y sostenibilidad de la agricultura en Colombia pueden ser influidas positivamente a través del aprovechamiento de la biodiversidad para la producción de bioinsumos. Fueron analizados a mediano y largo plazo, los posibles escenarios futuros generados por las regulaciones que intervienen en el avance tecnológico de los bioinsumos, a través de la aplicación de una encuesta Delphi, con la participación de 23 expertos, teniendo en cuenta las tres dimensiones del desarrollo sostenible. Sobre la base de este estudio, se encontró que el 65% de los expertos consideran que el impacto de la innovación o el desarrollo tecnológico del uso de bioinsumos en la producción agrícola, tiene un alto impacto económico con un nivel de concordancia significativo (≥0.05). Adicionalmente, el 65% seleccionó como el mejor escenario, en el cual se den condiciones que promuevan mayor desarrollo, acceso y aplicación de los bioinsumos, de tal forma que se incremente el ritmo de incorporación de la tecnología por parte de los productores. En conclusión, más allá del nivel de desarrollo tecnológico, es necesario revisar los procesos legislativos para la comercialización de los bioinsumos, fue evidente que el éxito futuro de la industria de la producción de productos biológicos dependerá de la gestión de empresas innovadoras, la eficiente comercialización de los mismos, la educación y transferencia a los productores y el progreso de la investigación.
Prospective analysis of agricultural bioinoculants in Colombia: an expert consultation
Artículos científicos
Keywords: Sostenibilidad; Agricultura orgánica; Biodiversidad; Desarrollo tecnológico; Producción agrícola; Research Subject Categories::FORESTRY, AGRICULTURAL SCIENCES and LANDSCAPE PLANNING::Plant production::Horticulture; Comercialización; Sustainability; Organic agriculture; Biodiversity; Technological development; Agriculture production; Commercialization